Overview Of The Value Of Ankle Brachial Index Of Type 2 Diabetes Mellitus In The Kabila Health Center Area Bone Bolango Regency - Fadiyah Faisal Anoez Alamri; Laksmyn Kadir; Ayu Rofia Nurfadillah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Type 2 diabetes mellitus is a chronic disease caused by impaired insulin secretion and insulin resistance, and is influenced by various risk factors such as age, diet, stress, and lack of physical activity. Complications caused by this disease include microvascular and macrovascular disorders, one of which is peripheral perfusion disorders that can be detected through an Ankle Brachial Index (ABI) examination. This study aims to determine the value of blood pressure and ABI in patients with type 2 diabetes mellitus in the working area of the Kabila Health Center, Bone Bolango Regency. The study used a descriptive quantitative method with a quasi experimental design and purposive sampling technique, involving 33 respondents. The results showed that 69.7% of respondents had high blood pressure and all respondents (100%) showed ABI values in the category of mild obstruction (0.71–0.89). These findings indicate that type 2 DM patients in the region are at risk of peripheral blood circulation disorders even though they have not shown severe clinical symptoms. Factors of age, physical activity, and the length of time you have been suffering from diabetes are factors that affect the value of ABI. It is recommended that future studies use larger samples and more accurate examination methods such as vascular doppler for more valid results.